DIGITAL MARKETING STRATEGY FOR NATURE BASED SUSTAINABLE TOURISM ON KABAENA ISLAND: GOOGLE MAPS ANALYSIS APPROACH - Eldo Delamontano; Cipta Endyana; Yunus Winoto; Evi Novianti (Forestry Study Program University Of Mataram, 2025)
Kabaena Island in Southeast Sulawesi has biodiversity, coastal landscapes, mountains and mineral content as the strength of sustainable development goals number 15 (SDGs 15). Currently, mining activities have had a negative impact on local communities in the economic, social, environmental, sanitation and health sectors due to natural degradation. This research aims to identify the tourism potential of Kabaena Island which can be promoted through digital strategies and design innovative digital marketing strategies to increase exposure of Kabaena Island tourism and support environmental sustainability. This research uses a qualitative descriptive analysis method to collect data using Google Maps analysis. A previous literature review shows that there is still minimal discussion regarding biodiversity and mineral content on Kabaena Island, which discusses the development of tourism destinations. Kabaena Island tourism development requires collaboration between government, academics and local communities to create sustainable development based on SDGs. The focus includes mining governance, creative economy, conservation and education, with digital marketing via Google Maps, destination branding and social media content. Collaboration with travel agents and business partners will support the local economy. Seminars or dissemination on sustainable development are important to strengthen governance and policies that support the community and preserve the environment.